2009
DOI: 10.3928/01477447-20090922-15
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodiatasis for the Treatment of Perthes' Disease

Abstract: It is hypothesized that the interruption of the blood supply is an important factor causing femoral head osteonecrosis in the early stages of Legg-Calvé-Perthes disease. Currently, treatment by containment is recommended to direct and guide remodeling of the softened femoral head as it evolves from fragmentation through ossification. The goal of this study was to show the results of arthrodiatasis to induce height recovery of the femoral head and to achieve true ambulatory nonweight-bearing containment. Forty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Given the lack of quantitative data, bilaterality of ONFH it was not possible to investigate separately. Finally, articles concern-Life 2022, 12, 179 9 of 12 ing Perthes disease have been excluded, as the management of these patients has been extensively analysed in the literature [70][71][72][73][74][75][76][77][78][79][80][81][82], and evidence on non-Perthes related ONFH is limited. Two studies which have been included for analysis reported data on patients with Perthes disease [31,33]; however, since the authors reported the results separately, data from patients with Perthes disease were not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of quantitative data, bilaterality of ONFH it was not possible to investigate separately. Finally, articles concern-Life 2022, 12, 179 9 of 12 ing Perthes disease have been excluded, as the management of these patients has been extensively analysed in the literature [70][71][72][73][74][75][76][77][78][79][80][81][82], and evidence on non-Perthes related ONFH is limited. Two studies which have been included for analysis reported data on patients with Perthes disease [31,33]; however, since the authors reported the results separately, data from patients with Perthes disease were not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from containment (which is most widely practiced) some surgeons have attempted arthrodiatasis or joint distraction with an external fixator in an attempt to unload the hip and facilitate the restoration of epiphyseal height. 45 46 The reported results have not been sufficiently encouraging to recommend this as the procedure of choice. 46 Yet another approach has been to drill the epiphysis in the hope that this will hasten re-vascularization; reports on the long term outcome of this method of treatment are awaited.…”
Section: T Reatment Of P Erthes mentioning
confidence: 93%
“…Several studies have evaluated the role of arthrodistraction in the treatment of Perthes' disease [12][13][14][15][16][17], but with discrete methodologies. Some authors included soft tissue release [16], whereas others used the non-articulated Ilizarov system [15].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there has been some evidence to suggest that distraction forces applied to the hip joint can offer mechanical protection to the femoral head and promote bone revascularisation [12][13][14][15][16][17]. Therefore, hip joint distraction may offer an alternative therapeutic option for patients with Legg-Calvé-Perthes disease (otherwise called Perthes' disease), as it represents an attractive link between mechanical and biological processes.…”
Section: Introductionmentioning
confidence: 99%